â€œImplementasi Peraturan Daerah Kabupaten Banjarnegara Nomor 7 Tahun 2013 tentang Peran Masyarakat dalam Bidang Pendidikanâ€ - Sefrina, Giandika Estri; Suwitri, Sri (Journal of Public Policy and Management Review, 2019)
The implementation of Local Regulation Banjarnegara District Number 7 Year 2013 about Role of Society in Education Sector aims to improve the quality of education in Banjarnegara district. There are still problems that occur in education in Banjarnegara district which cannot be separated from the role of the community as the provision of educational resources, the implementation of educational units, and the use of educational outcomes. The purpose of this study is to describe and analyze the implementation of Local Regulation Banjarnegara District Number 7 Year 2013 about Role of Society in Education Sector, and to identify the supporting and inhibiting factors for the implementation of Local Regulation Banjarnegara District Number 7 Year 2013 about Role of Society in Education Sector. The researcher used an implementation model that researcher compiled with a Top-Down approach based on the Van Meter Van Horn theory, Merile S. Grindle, and Daniel Mazmanian and Paul A. Sabatier. The factors that researcher use in discussing the implementation of the regional regulations studied are standards and policy targets, resources, communication between organizations, as well as social, economic, political conditions. The results showed that the implementation of Local Regulation Banjarnegara District Number 7 Year 2013 was not optimal due to the influence of the factors of lack of clarity on standards and targets for regional regulations, lack of human resources, and facilities and economic, social, and political factors of Banjarnegara society.Suggestions that researchers provide are by increasing teacher competence, fulfilling educational facilities and infrastructure, conducting socialization in schools to increase awareness of education, and optimizing Operational Assistance School.